THE EFFECTIVENESS OF THE PROBLEM-BASED LEARNING MODEL ON GEOGRAPHY LEARNING OUTCOMES - Hastuti, Karunia Puji; Alviawati, Eva; Aristin, Nevy Farista; Arisanty, Deasy; Abbas, Ersis Warmansyah; Chaniago, Syahril; Masitah, Masitah (Universitas Lambung Mangkurat, 2023)
This research aims to determine the effectiveness of problem-based learning models on geography learning outcomes. The study used a quasi-experimental design with a non-equivalent control group design. The sampling method is purposive sampling with samples of class X IPS 1 as the experiment class and class X IPS 2 as the control class. The techniques in data collection used are tests, questionnaires, observations, and documentation. The data analysis used is descriptive statistical analysis and inferential statistics. The results show a difference between learning outcomes using a problem-based model and learning outcomes without problem-based models. The problem-based learning model is effective in learning outcomes of Geography class X social studies SMA Negeri 1 Rantau Badauh. Student learning outcomes in the experimental type have increased significantly because, in the learning process, students play an active role in finding the concept of learning materials so that students can apply these concepts to identify existing problems. Problem-based learning model provides a more concrete learning experience so that the understanding students get in learning is not limited to textual but to a broader mastery of the material.